2013
DOI: 10.1097/ta.0b013e3182a74a5b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation weaning and extubation after spinal cord injury

Abstract: BACKGROUND Respiratory failure after acute spinal cord injury (SCI) is well recognized, but data defining which patients need long-term ventilator support, and criteria for weaning and extubation are lacking. We hypothesized that many patients with SCI, even those with cervical SCI, can be successfully managed without long-term mechanical ventilation and its associated morbidity. METHODS Under the auspices of the Western Trauma Association Multi-Center Trials Group, a retrospective study of patients with SCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 15 publications
2
41
0
1
Order By: Relevance
“…Others have suggested that not all patients with cervical spine injuries should undergo ET. 24 Although this study is difficult to interpret because of mixing of patient populations, the authors' suggestion should make the practicing clinician question the use of ''automatic'' tracheostomy for all patients with cervical SCI. In an attempt to elucidate the factors involved, we analyzed the small percentage of patients with complete cervical SCI that did not require prolonged MV.…”
Section: Commentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Others have suggested that not all patients with cervical spine injuries should undergo ET. 24 Although this study is difficult to interpret because of mixing of patient populations, the authors' suggestion should make the practicing clinician question the use of ''automatic'' tracheostomy for all patients with cervical SCI. In an attempt to elucidate the factors involved, we analyzed the small percentage of patients with complete cervical SCI that did not require prolonged MV.…”
Section: Commentsmentioning
confidence: 98%
“…24 When reviewing our own experience with cervical SCI, we separated these 2 distinct subsets of patientsdcomplete versus incomplete spinal cord injuries. Patients with thoracic and lumbar spine injuries were purposefully not included in the study.…”
Section: Commentsmentioning
confidence: 99%
“…Individuals with acute complete tetraplegia are particularly vulnerable to respiratory failure during the acute phase resulting from the combined effect of spinal shock leading to flaccid chest wall muscles, denervation of the ventilatory muscles, presence of concomitant lung injuries, potential decreased respiratory drive due to concomitant head injuries and narcotic analgesic, and cervical soft tissue edema associated with the surgery [5]. Between 40 and 80% of subjects with acute complete tetraplegia may therefore require mechanical ventilation (MV) support during the acute care [6][7][8]. As prolonged oral/nasal endotracheal tubes is detrimental, tracheostomy placement is required in 10-60% of patients following tetraplegia [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Akut dönemde MV'e bağlanmış olguların ekstübasyonu, uzun süreli MV desteğine karar verme ve trakeostomi zamanlaması konusunda yeterli kanıt olmadığından bu konudaki uygulamalar çeşitlilik gösterir (32) . Eve MV ile gönderilen olguların büyük kısmının hastanede iken ekstübe edilebileceğini gösteren çalışmalar mevcuttur (32,33) . Spinal hasardan öte uzamış ventilatör desteğinin kendi MV bağımlığının nedeni olabilir.…”
Section: Obezi̇te Ve MV Desteği̇unclassified